Clinical experience with dalbavancin for the treatment of deep sternal wound infection. (September 2019) - Bartoletti, Michele; Mikus, Elisa; Pascale, Renato; Giannella, Maddalena; Tedeschi, Sara; Calvi, Simone; Tenti, Elena; Tumietto, Fabio; Viale, Pierluigi
Highlights: Dalbavancin treatment for deep sternal wound infection shows good clinical outcomes. The long half-life of dalbavancin allows once-weekly dosing. Dalbavancin treatment allows early discharge. Abstract: Objectives: Deep sternal wound infection (DSWI) is a complication of major heart surgery with high morbidity as well as prolonged antimicrobial treatment and hospital length of stay (LoS). Dalbavancin is a new lipoglycopeptide antibiotic active against Gram-positive micro-organisms, including methicillin-resistant Staphylococcus aureus (MRSA), with a long half-life. This small case series assessed the feasibility of dalbavancin for the treatment of DSWI. Methods: This was retrospective, observational, cohort study of patients treated with dalbavancin for DSWI over a 2-year period (March 2016 to April 2018) in two cardiac surgery departments in Italy. All patients with DSWI underwent surgical accurate debridement. Dalbavancin was administered during the hospital stay or in an outpatient facility. Results: Among 15 patients enrolled in the study, MRSA was isolated in 7 (47%), methicillin-resistant Staphylococcus epidermidis in 6 (40%) and other coagulase-negative staphylococci in 2 (13%). Dalbavancin was administered by two infusions in 9 patients (60%), whereas 5 patients (33%) received a median of four doses. Fourteen patients received a first dose of 1000 mg followed by 500 mg, whereas one patient received two doses of 1500 mg each. All patients were defined as clinically cured. The median hospital LoS was 13 days (interquartile range, 8–18 days). At 6 months after discharge, 14 patients (93%) showed no relapse of DSWI, whereas 1 patient recurred with a diagnosis of DSWI caused by another pathogen ( Candida sp.). Conclusion: Dalbavancin may be an alternative option for DSWI caused by Gram-positive bacteria when first-line treatments are contraindicated or as salvage treatment.